(untitled) (International Journal of Language, Literacy and Translation, 2025)
This study explores the impact of self-directed English listening activities on the autonomy of Chinese EFL undergraduates. The research is guided by four main questions: (1) How do self-directed listening activities contribute to autonomy? (2) Which self-directed listening activities do undergraduates prefer and find most impactful? (3) What challenges emerge during these activities? (4) How can strategies address these challenges and optimise autonomy in English listening learning? The study involves English major undergraduates and employs mixed methods to collect both quantitative and qualitative data. Surveys and interviews are utilized for data collection, with surveys gauging preferences, effectiveness, and challenges and interviews providing deeper insights. Quantitative analysis, using descriptive statistics, identifies trends in the data, while qualitative thematic analysis uncovers patterns within the interview responses. The findings of this study aim to inform educators, curriculum designers, and policymakers, offering practical implications to enhance English listening teaching by assessing the efficacy of self-directed English listening activities in promoting autonomy. Empowering EFL students to take control of their language learning journey is crucial, and this research contributes valuable insights to achieve this goal. By examining the preferences, impacts, and challenges associated with self-directed listening activities, the study provides practical guidance for educators to optimise autonomy in English learning environments. Ultimately, the research contributes to the ongoing efforts to improve English language education for Chinese EFL undergraduates.